Cyanobacterial blooms in the Po River basin and the eastern Alps - Fabio Buzzi; Chiara Agostinelli; Renata Alber; Andrea Beghi; Eugenia Bettoni; Enrico Bressan; Ketty Caraffini; Elisa Carena; Francesca Caviglia; Matteo Dossena; Pier Luigi Fogliati; Riccardo Formenti; et al. (Advances in Oceanography and Limnology)
In this paper, we briefly describe episodes of cyanobacterial blooms that have occurred in lakes of northern Italy since 2000. In addition to listing the species involved in these blooms, we provide information on the trophic and ecological status of the water bodies and the presence of algal toxins. Furthermore, we report an example of a risk assessment effort aimed at developing a quality control system for water intended for human consumption. The use of high-frequency monitoring techniques, integrated with predictive modelling, remote sensing, and molecular analysis for species identification, is becoming increasingly important in the context of the effects of ongoing climate change.